Adoption model for cloud-based E-learning in Omani higher education institutions - Hassan Alajmi, Qasim Abdullah (2019)
Today, there is a developing pattern with respect to the utilization of e-learning approach in the Higher Education Institutions (HEIs). E-learning framework requires immense up-front infrastructure with numerous establishment which is not easy to be managed. Cloud computing comes with a new development platform to overcome e-learning issues in an easy and cost-efficient way. Today, HEIs are facing numerous challenges to be in line with the rapid transformation which is essential to globalization and new technology adoption. Based on the literature, most significant obstacles were the cost of up-front infrastructure, maintenance, upgrading and competent of Information Systems (IS) staff to handle daily technical support. Thus, the conventional e-learning method is no longer enough due to the above-mentioned obstacles and barriers. In the other end, Cloud-Based E-Learning (CBEL) is an attractive e-learning platform that provides a flexible and scalable e-learning framework which can be accessed anywhere, anytime and by any device. This research investigated the most significant factors influencing CBEL adoption by HEIs globally and in Oman as a case study. The conceptual framework of this study has been built based on three dimensions; Technological evaluation, Readiness evaluation, and Information culture factors. These dimensions were extracted from two renowned technology adoption theories, Fit-Viability Model (FVM) and Diffusion of Innovation (DOI). Another dimension considered is Information culture (IC) factors which were selected based on its significant influence on any technology adoption and this is relevant to the objectives of this study. In all, fourteenth proposed hypotheses were developed to examine its significant influence on the adoption and examined to test the fitness of the developed model for CBEL to the HEIs in Oman and its viability as well. Structured questionnaires which consists of standardized questions with fixed scale, it were used for the primary data collection from a sample of academics and IT professional staff from 32 HEIs in Oman. The population for this study was knowledgeable about cloud computing services and its features and models. Statistical Package for Social Science (SPSS v. 25) and Partial Least Squares (SmartPLS v.3) we reused as analysis tools to evaluate the developed CBEL model factors and to examine the relationship among them. The final model was provided based on the result of the findings which proved that Fit, Viability, and Information culture factors significantly influenced the decision for CBEL adoption by HEIs in Oman. Task, Relative Advantages, Complexity, and Compatibility influenced the fitness as technical factors. The final model showed that 68.2% of the significant factors for the adoption of CBEL was covered, and by adopting this model, 56.1% of improvement can be achieved in the quality of academic services. The suggested level of significant Path coefficient (β) value is 0.1, while in this study, were at t-statistics 1.217 and 16.967. The key significant of this study is that, HEIs can adopt CBEL with more confidence, reducing the foundation cost, and decreasing the waiting time to deliver e-learning services to their students with quality consideration.